O-004 Application of Population Pharmacokinetic Modeling to Develop Individualized Infliximab Dosing Strategies in Pediatric Crohn's Disease. (February 2017) - Frymoyer, Adam; Hoekman, Daniel; de Meij, Tim; Hummel, Thalia; Benninga, Marc; Kindermann, Angelika; Piester, Travis; Park, KT
Abstract : Background: Adequate infliximab (IFX) exposure is critical when treating Crohn's disease (CD), and trough concentrations <3 μg/mL are associated with loss of response. However, the pharmacokinetics of IFX are highly variable in children with CD, and this has made IFX dosing challenging in this population. Model-based drug dosing offers the potential for developing individualized dosing strategies. The objective of the current study was to evaluate the predictive performance and clinical utility of a previously published population pharmacokinetic model of IFX when applied to children with CD. Methods: We conducted a secondary analysis of a prospective cohort of children <18 years with CD receiving IFX maintenance treatment at 3 Dutch hospitals. IFX trough concentrations were measured prior to 2 consecutive IFX infusions. Implementing the published population pharmacokinetic model in the nonlinear mixed-effects modeling software NONMEM, individual Bayesian pharmacokinetic parameters were estimated in each patient using their dose history, IFX concentrations, and patient specific characteristics (i.e., weight, serum albumin, concomitant immunomodulator therapy, and infliximab antibody status [ATI]). Predicted IFX concentrations were then calculated in each patient using his/her individual Bayesian pharmacokinetic parameters and were compared to the actual measured IFX concentrations. In addition, to assess individual dose needs, doses of 5, 7.5, and 10 mg/kg and dosing intervals of every 4, 6, and 8 weeks were examined in each patient to assess dose-trough concentration relationships. Results: A total of 34 children with CD were studied with a median (IQR) age 14.9 (13.2–15.9) years, weight 53 (48–62) kg, albumin 4.3 (4.0–4.5) g/dL, and CRP 2.4 (0.9–4.8) mg/L. Three (10%) patients had ATI and 15 (44%) received concomitant immunomodulator therapy. The median % prediction error (i.e., measure of bias) of IFX concentrations predicted by the model was 5.6% (95% CI, 2.3%–8.7%) and the median absolute % prediction error (i.e., measure of precision) was 10.7% (95% CI, 7.4%–13.3%). Predicted concentrations were within ±1.0 and ±1.5 μg/mL of the actual measured concentrations for 88% and 95% of measurements, respectively. At the standard IFX maintenance dosing of 5 mg/kg every 8 weeks, the median predicted trough concentration was 2.2 μg/mL and variation between patients was high (CV% 68%). A trough concentration >3 and >5 μg/mL was predicted to be achieved in 32% and 6% of patients, respectively, with standard dosing. To achieve a trough >3 and >5 μg/mL, a dosing interval ⩽ every 6 weeks was predicted to be required in 29% and 62% of patients, respectively. Conclusions: A published IFX population pharmacokinetic model demonstrated accurate predictive performance in a pediatric CD population who had IFX trough concentrations measured. Individualized IFX dosing strategies in children with CD will be critical to consistently achieve trough concentrations associated with optimal outcomes. More robust, model-based clinical dosing support tools are needed to help guide clinicians with dose individualization.